Iron Binding Modulates Candidacidal Properties of Salivary Histatin 5. (January 2015) - Puri, S.; Li, R.; Ruszaj, D.; Tati, S.; Edgerton, M.
Salivary protein histatin 5 (Hst 5) is fungicidal toward Candida albicans, the causative agent of oropharyngeal candidiasis. However, its activity in saliva is compromised by salivary protease-mediated degradation and interaction with salivary salts. Hst 5 has also been shown to bind various metals in saliva—namely, Zn, Cu, and Ni. Surprisingly, interactions of Hst 5 with Fe have not been studied, although iron is one of the most abundant metals present in saliva. Using circular dichroism, we show that Hst 5 can bind up to 10 equivalents of iron as measured by loss of its alpha-helical secondary structure that is normally observed for it in trifluoroethylene. A significant decrease in the candidacidal ability of Hst 5 was observed upon iron binding, with increasing iron concentrations being inversely proportional to Hst 5 killing activity. Binding assays showed that the decrease in killing was likely a result of reduced binding (10-fold reduction) of Fe–Hst 5 to C. albicans cells. Protease stability analysis showed that Fe–Hst 5 was completely resistant to trypsin digestion. In contrast, zinc binding had limited effects on Hst 5 fungicidal activity or protease susceptibility. RNA sequencing results identified changes in iron uptake genes in Hst 5–treated C. albicans cells. Our findings thus suggest that consequences of Hst 5 binding iron not only affect candidacidal ability and proteolyic stability of Hst 5, but may also contribute to a novel killing mechanism involving interference with cellular iron metabolism.